Exploring a spatial–temporal understanding of organizational learning. Issue 1 (February 2015) - Rowe, Andrew
This article responds to calls for research into the production of time-space in organizations – in particular, it does so as a way of synthesizing the diverse ways of thinking in the existing organizational learning literature. This is achieved by drawing upon Lefebvrian-informed research into spatial–temporal rhythms, enabling the investigation of the rhythmic production and reproduction of time-spaces from a 12-month ethnography of a UK Management Team. This rhythmic approach also augments extant spatial and temporal organizational research. It reveals how learning involves contrary spatial–temporal experiences – highlighting the interplay of rhythms, which raises reflexive implications for both managers and researchers.